The Pragmatic Impact of Background Emotional Memory on Interpersonal Relations - Paronyan, Shushanik; Rostomyan, Anna (Armenian Folia Anglistika, 2011)
The article studies the role of the background knowledge and particularly that of emotional memory on speech interpretation and formation. The examination of the factual material is carried out through the cognitive and pragmatic concept. Emotions expressed in speech and having a significant impact on the interpersonal relations of the interlocuters are viewed not only as sensory factors, but also as elements belonging to the cognitive sphere of speech.